Windfall - Smith, Jennifer E., 1980- (New York : Delacorte Press, 2017)
"Alice loves Teddy, her best friend, but has never told him. When she buys him a lottery ticket that turns out to be a winner, their lives are changed forever and their friendship is put to the ultimate test"--
Keywords: Love -- Fiction; Friendship -- Fiction; Lotteries -- Fiction; Luck -- FIction; Wealth -- Fiction; Orphans -- Fiction; Friendship -- Fiction; Lotteries -- Fiction; Fortune -- Fiction; Wealth -- Fiction; Lottery winners -- Fiction; Life change events -- Fiction; Luck -- Fiction; Friendship -- Fiction; Wealth -- Fiction; Love -- Fiction; Romance fiction